Revenue management in Portuguese 4- and 5- star hotels - Carvalho, Miguel Coimbra Sandinha de (2024)
This study aims to contribute to the Revenue Management literature, by investigating how it is applied in 4- and 5-star hotels in Portugal. It explores the importance of RM, which practices are most frequently used and regarded as more important, and their impact on hotel efficiency. In addition, it examines AI's expected future role in RM. Following a mixed method approach, the research highlights RM's importance to hotel performance and key practices like market analysis, dynamic pricing, and KPI analysis. It anticipates AI's significant future role in RM. These results offer valuable insights for revenue professionals in the hospitality sector.